(untitled) (European Journal of Pure and Applied Mathematics, 2017)
We study (Ï•, Ï•Â´)-holomorphic and harmonic maps on almost contact metric manifolds satisfying dÎ· + dÎ·oÏ• âŠ— Ï• = 2Î¦. It should be noted that these manifolds are not necessarilyÂ contact metric manifolds. Examples of such manifolds are nearly Sasakain and quasi contactÂ metric manifolds.